Firing Patterns of Leech Heartbeat Interneurons Under External Current Stimulation: a Model Study - Ju, N.; Liu, Sh.Q.; Lu, B.; Jiang, X. (Нейрофизиология, 2015)
Leech heartbeat interneurons (HN cells) interconnected by inhibitory synapses have
been simulated using several modified models based on the Hodgkin-Huxley equations;
yet, adequate characteristics of HN cells are hardly possible to be summarized due to the
complexity of these models. The Winnerless Competition (WLC) model created as an
inhibitory-connected nervous network is more appropriate for networks consisting of HN
cells. We investigated different firing patterns produced by such model under application
of various stimuli simulating changes in the leech’s environment. By means of recording
the firing frequency, synchronization, interspike intervals (ISIs), and maxima of action
potentials (APs) and also by application of the theory of mixed-mode oscillations (MMOs),
different properties of firing patterns in HN cells were examined. According to the results
of computational analyses, DC and AC stimulations were found to play different roles in
modulating the leech’s heartbeat rhythm; external stimuli could influence the intensity and
duration of the network reaction by changing both AP frequency and amplitude. Besides,
changes in the recovery abilities of neurons can lead to various release modes of HN cells.
Combined with physiological experiments on medical leeches, numerical analysis allows
us to gain a deeper understanding of how HN cells coordinate with each other to bring the
rhythm to the leech heartbeat system. Інтернейрони генератора серцевого ритму (HN-нейрони)
п’явки, зв’язані гальмівними синапсами, піддавалися моделюванню з використанням декількох модифікованих моделей, основаних на рівняннях Ходжкіна – Хакслі, проте
адекватні характеристики HN-клітин було важко відтворити
через складність таких моделей. Для моделювання мереж,
до яких входять HN-клітини, більш придатною є так звана
Winnerless Competition-модель, розроблена для симулювання мереж із нейронів, які поєднані гальмівними зв’язками.
Ми досліджували різни патерни розрядів, генерованих такою моделлю, в умовах прикладання різних струмових стимулів, імітуючих зміни в середовищі мешкання п’явки. Реєстрація частот розрядів, їх синхронізації, міжімпульсних
інтервалів, максимумів потенціалів дії (ПД) , а також застосування теорії мішаного режиму осциляцій дозволило
дослідити різні властивості патернів розрядів HN-клітин.
Згідно з результатами комп’ютерного аналізу, стимуляції
постійним та змінним струмами, як виявилося, відіграють
різну роль у модуляції серцевого ритму п’явки; зовнішні
стимули можуть впливати на інтенсивність та тривалість
реакції мережі, змінюючи як частоту, так і амплітуду ПД.
Окрім того, зміни в здатності нейронів до відновлення можуть призводити до різних варіантів розрядів HN-клітин.
Поєднання фізіологічних експериментів на п’явках та модельного комп’ютерного аналізу дозволяє дійти глибшого
розуміння, яким чином HN-клітини координують свою активність у перебігу формування ритму в системі керування
скороченнями «серця» у цієї тварини.